For a discursive-linguistic approach to junction: analysis of linking mechanisms in narrative and argumentative discursive traditions: Para uma abordagem linguístico-discursiva da junção: análise dos mecanismos de junção nas tradições discursivas narrativa e argumentativa - Lopes-Damasio, Lúcia Regiane; Santana, Mateus Dias (Revista do GEL, 2024)
This paper presents the results of a quantitative-qualitative analysis of linking mechanisms (LMs) in narrative and argumentative discursive traditions (DTs), focusing on the relation between subject and language based on (their) image of the written mode of enunciation. The study is based on the concept of constitutively heterogeneous writing (Corrêa, 1997), on the textual-dialogical view, grounded on the concept of DTs (Kabatek, 2006), and the functionalist model of junction (Raible, 2001). LMs are therefore considered to be traces of the subject’s circulation through writing, within a linguistic-discursive approach. The results of this approach show that parataxis prevails in both DTs, according to the meaning of addition, cause, later time and contrast. This takes place in junction spaces which indicate, with a higher frequency in these traditions, the subject’s circulation within the sphere of the genesis of writing, in junction traces marked with higher repeatability by juxtapositions and the use of the conjunction and, as gestures which point towards the context of enunciation.